Design and analysis of novel flexible riser configurations - Mohammed Lukman Haji Omar. (2009)
Flexible risers either made of bonded or non-bonded high strength steel or other alloy materials have been increasingly utilised for a high pressure dynamic environment over the past 30 years or so in the offshore industry. Through the years, as part of a floating production system, developments in the design of flexible risers configurations have made the exploitation of oil/gas resources in deep waters with hostile environments economically viable. As these configurations are intimately dependant on the environment situation, different types of configurations are established to best adapt different situations. In this report, some aspects of the design of static and dynamic flexible riser configurations are discussed.